East Asian Visions : Perspectives on Economic Development - Gill, Indermit; Huang, Yukon; Kharas, Homi (Washington, DC : World Bank, 2012)
East Asian Visions: Perspectives on Economic Development is a collection of essays by 17 eminent East Asians who represent a broad spectrum of backgrounds and experiences. All are senior policy makers, statesmen, or scholars who have either had to deal with or think through some of the most critical financial and developmental issues confronting their countries and the region. Collectively, 10 of them have, at some point in their careers, been at the head of key ministries and central banks; nearly a dozen have been academics and scholars of distinction; several have served as ambassadors to the West and bring a more global strategic perspective; and many have been influential policy advisers and decision makers in governments and international financial agencies. Their essays reflect individual experiences at critical economic junctures and are occasionally quite personal, not surprising since each author selected a topic of his or her own choosing. Given their backgrounds, they have chosen to write about the highly diverse country experiences of East Asia, covering rich, middle income, and poor countries, and they speculate on how their countries fit into a rapidly changing region and globalizing world. Four themes permeate these essays: explaining East Asia's growth and developmental success; the powerful forces of regional integration and building efficiency versus vulnerability; avoiding domestic disintegration given growing public intolerance of increasing inequities, pollution, and corruption; and where will East Asia find its next generation of leaders.